2018
DOI: 10.18203/issn.2454-5929.ijohns20185303
|View full text |Cite
|
Sign up to set email alerts
|

A review of pharyngeal mucosal closure technique in total laryngectomy

Abstract: <p class="abstract"><strong>Background:</strong> The purpose of this retrospective analysis was to review our single institute based experience with the pharyngocutaneous fistula following total laryngectomy and to determine the impact of pharyngeal closure technique in the development of PCF in our patients.</p><p class="abstract"><strong>Methods:</strong> The medical records of the patients, who underwent total laryngectomy for squamous cell carcinoma of the larynx a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
1
0
2
Order By: Relevance
“…Twelve studies were identified comparing the shape of manual suture, which included primary [ 25 , 31 – 33 ] and mixed primary/salvage TL [ 34 41 ] (Table 2 ). Bril et al [ 42 ] did not report specific rates of PCF and the study was thus excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies were identified comparing the shape of manual suture, which included primary [ 25 , 31 – 33 ] and mixed primary/salvage TL [ 34 41 ] (Table 2 ). Bril et al [ 42 ] did not report specific rates of PCF and the study was thus excluded.…”
Section: Resultsmentioning
confidence: 99%
“…So với các nghiên cứu đã được thực hiện tại Việt Nam, tuổi trung bình trong nghiên cứu của cúng tôi không có sự khác biệt [9], [11]. Tuổi trung bình trong nghiên cứu của chúng tôi cũng tương đương với một số nghiên cứu nước ngoài [4], [8].…”
Section: đặC đIểm Chung Của Dân Số Nghiên Cứuunclassified
“…Điều này phù hợp với y văn và các nghiên cứu trong và ngoài nước là nam bị UTTQ nhiều hơn nữ. Kết quả nghiên cứu của chúng tôi không có sự khác biệt so với các kết quả nghiên cứu trong nước [9] và ngoài nước [4], [8]. Nhiều tác cho rằng nữ giới ít bị UTTQ là do ít tiếp xúc với các yếu tố có liên quan đến gây bệnh hơn so với nam giới.…”
Section: đặC đIểm Chung Của Dân Số Nghiên Cứuunclassified